Myricetin activates the Caspase-3/GSDME pathway via ER stress induction of pyroptosis in lung cancer cells - Han, Jicheng; Cheng, Cheng; Zhang, Jinxin; Fang, Jinbo; Yao, Wei; Zhu, Yilong; Xiu, Zhiru; Jin, Ningyi; Lu, Huijun; Li, Xiao; Li, Yiquan (Frontiers in Pharmacology, 2022)
Pyroptosis is related to the occurrence, development, and therapeutic response of tumors, mediated by the proteins of the Gasdermin family. These proteins have become potential biomarkers for cancer treatment, and their agonists are likely to become a new direction in research and development of antitumor drugs. In this study, we found that myricetin has an inhibitory effect on lung cancer cells of the activation of pyroptosis. Analysis of the expression of Gasdermin family proteins revealed that this phenomenon was caused by the cleavage of GSDME. Subsequently, specific inhibitors, we found that caspase-3 was its upstream activation factor. In addition, mitochondrial and endoplasmic reticulum (ER) analysis showed that myricetin can cause ER stress and increase reactive oxygen species (ROS) levels. Subsequent inhibition of caspase-12 revealed that the expression levels of cleaved-caspase-3 and cleaved-GSDME were significantly reduced, resulting in the inhibition of pyroptosis. Using in vivo experiments, we also found that the treatment with myricetin can reduce tumor volume and significantly increase the level of pyroptosis-related proteins in tumor tissues. Overall, our findings show that myricetin induces cell death of lung cancer cells primarily through an ER stress pathway-induced pyroptosis. Therefore, myricetin has the potential to be used as a pyroptosis agonist in research and development of antitumor drugs.